Determination of the maximum penetration level of Auxiliary Service Voltage Transformer Sub-stations on 132kV Transmission Network - Kitheka, Joel (My University, 2017)
The overall electricity access rate is still very low in most sub-Saharan African (SSA) countries. The rate is even lower in rural areas where most of the population in these countries live. One of the main obstacles to rural electrification (RE) is the high cost of laying the distribution infrastructure owing to the dispersed nature of loads and low demand. Thus, electrifying the rural areas needs to be considered holistically and not just on the financial viability. To reduce cost, it is important that auxiliary service voltage transformer (ASVT), which are cheaper than the conventional substation be explored. ASVT have been tried successfully in some parts of the world like Congo and Mexico. However the literature review showed that no work had so far been done with regard to determination of the penetration point and maximum penetration level of these technologies on power transmission networks. These ASVT sub-stations have the ability to tap power directly from high voltage transmission lines of either 132kV or 220kV and step it down to 240V for single phase distribution. This research investigated the penetration point and maximum penetration level of ASVT sub-stations in power transmission networks with regard to transmission line voltage profile. The research was done by simulating ASVT sub-station models terminated in High Voltage transmission lines using SIMULINK software. The realized voltage levels were compared with the expected H.V transmission line voltage levels to determine whether the voltage profile had been violated. The ASVT loadability curves and the constructed Surge Impedance Loading (SIL) curves were used to ascertain voltage stability of the system. The research revealed that the first ASVT sub-station can be terminated at any point on the H.V transmission line without violating voltage profile. The simulation further revealed that a maximum of nine ASVT sub-stations can be terminated on a 440km, 132kV transmission line without violating the voltage profile of the transmission network.